Dying Is Unexpectedly Positive. (July 2017) - Goranson, Amelia; Ritter, Ryan S.; Waytz, Adam; Norton, Michael I.; Gray, Kurt
In people's imagination, dying seems dreadful; however, these perceptions may not reflect reality. In two studies, we compared the affective experience of people facing imminent death with that of people imagining imminent death. Study 1 revealed that blog posts of near-death patients with cancer and amyotrophic lateral sclerosis were more positive and less negative than the simulated blog posts of nonpatients—and also that the patients' blog posts became more positive as death neared. Study 2 revealed that the last words of death-row inmates were more positive and less negative than the simulated last words of noninmates—and also that these last words were less negative than poetry written by death-row inmates. Together, these results suggest that the experience of dying—even because of terminal illness or execution—may be more pleasant than one imagines.